THE IMPLEMENTATION OF YOUTUBE-BASED LEARNING MEDIA TO IMPROVE LISTENING SKILLS OF EIGHTH-GRADE STUDENTS AT STATE ISLAMIC JUNIOR HIGH SCHOOL PALOPO - Rita Andriani; Rusdianto; Mawardi; Mustafa (Universitas Islam Negeri Palopo, 2025)
This study aimed to examine the implementation of YouTube-based learning media in ‎improving students' maharah istima' (Arabic listening skills) and to analyze the ‎improvement in the listening competence of eighth-grade students at Madrasah ‎Tsanawiyah Negeri Palopo. The study employed Classroom Action Research based on ‎the Kemmis and McTaggart model, consisting of planning, action, observation, and ‎reflection conducted in two cycles. The participants were 25 students of Class VIII-C. ‎Data were collected through observation, tests, and documentation and analyzed using ‎descriptive quantitative and qualitative techniques. The findings revealed that the ‎implementation of YouTube-based learning media significantly improved students' ‎listening skills. The average score increased from 42.72 in the pre-cycle stage with 0% ‎classical mastery to 62.00 in Cycle I with 28% classical mastery and further increased to ‎‎78.20 in Cycle II with 92% classical mastery. These findings indicate that YouTube ‎provides engaging audiovisual learning experiences that facilitate students' ‎understanding of Arabic vocabulary, pronunciation, and spoken texts. Therefore, ‎YouTube-based learning media can serve as an effective instructional alternative for ‎enhancing students' maharah istima', while simultaneously promoting active ‎participation and learning motivation in Arabic language instruction.‎